Combined hydrogen and oxygen therapy attenuates vascular cognitive impairment in rats via gut microbiota-derived SCFA-GPR41/PI3K/Akt/Nrf2 signaling - Xinle Fu; Mengzhuo Ma; Yujie Zhang; Yanzhuo Gao; Yuan Li; Jing Luan; Yingying Fan; Yifei Wang; Xiaoya Xue; Ling Ma; Yizhuo Liu; Hao Xu (Scientific Reports, 2026)
Abstract Vascular cognitive impairment (VCI), a consequence of chronic cerebral hypoperfusion (CCH), is characterized by neuroinflammation and neuronal apoptosis. Hydrogen-rich and hyperoxygenated solution (HHOS) may attenuate CCH-induced brain injury through antioxidant, anti-inflammatory, and gut microbiota-modulating mechanisms. This study investigated the neuroprotective effects of HHOS via the GPR41/PI3K/Nrf2 pathway, comparing its efficacy to hyperoxygenated solution (HOS) and hydrogen-rich solution (HRS) alone. We found that HHOS significantly improved spatial memory and reduced anxiety-like behaviors in BCCAO rats. It also attenuated hippocampal neuronal apoptosis (reduced TUNEL-positive cells) and microglial activation (decreased Iba-1 expression level), enriched SCFAs-producing gut microbiota (e.g. Clostridia_UCG-014 , Bacteroides ) and activated the SCFAs/GPR41/PI3K/Nrf2 pathway, upregulating antioxidant proteins (HO-1, GST). HRS partially restored microbiota and reduced apoptosis, while HOS showed limited efficacy. Collectively, HHOS outperformed monotherapies by coupling microbiota-SCFA restoration with GPR41/PI3K/Akt/Nrf2-mediated antioxidant defense, supporting a novel dual-gas strategy for VCI.